Implementation (PBKM) of Skill-Based Learning Through Micro Teaching in Improving the Competency of PAI Students at IAIN Madura - Nailatur Rizqiyah; Waqiatul Masruroh; Masti Yanto (Jurnal Ilmiah Ekonomi dan Manajemen Indonesia, 2025)
Teaching skills are an ability that every teacher must have in order to make it easier to convey knowledge to their students. The Islamic Religious Education (PAI) study program is a study program that requires its students to have optimal teaching skills. In improving the teaching skills of PAI students, IAIN Madura implements teaching skills-based learning through micro teaching. Therefore, this study aims to determine the implementation of teaching skills-based learning through micro teaching in improving the competence of PAI students at IAIN Madura. This research uses a descriptive type of qualitative method. The subject of this research is the students of PAI study program at IAIN Madura. The findings of this study are how the implementation of micro teaching-based learning can run smoothly so as to equip students with teaching skills before actually plunging into the real world of work. This article concludes that the implementation of PBKM through micro teaching is able to provide good teaching skills to students where it is very useful for students in facing the world of work, especially in teaching.